(:unas) unassigned - Oliveira, Iago Lessa [UNESP]; Santos, Gabriel Bertacco [UNESP]; Gasche, José Luiz [UNESP]; Militzer, Julio; Baccin, Carlos Eduardo (ASME, 2021)
When simulating blood flow in intracranial aneurysms (IAs), the Newtonian model seems to be ubiquitous. However, analyzing the results from the few studies on this subject, the doubt remains on whether it is necessary to use non-Newtonian models in Computational Fluid Dynamics (CFD) simulations of cerebral vascular flows. The objective of this study is to investigate whether different rheology models would influence the hemodynamic parameters related to the wall shear stress (WSS) for ruptured and unruptured IA cases, especially because ruptured aneurysms normally have morphological features, such as lobular regions and blebs, that could trigger non-Newtonian phenomena in the blood flow due to low shear rates. By using CFD in an open-source framework, we simulated 4 ruptured and 4 unruptured patient-specific aneurysms to assess the influence of the blood modeling on the main hemodynamic variables associated with aneurysm formation, growth, and rupture. Results for WSS and oscillatory shear index (OSI) and their metrics were obtained using Casson and Carreau-Yasuda non-Newtonian models and were compared with those obtained using the Newtonian model. We found that all differences between non-Newtonian and the Newtonian models were consistent among all cases irrespective of their rupture status. We further found that the WSS at peak systole is overestimated by more than 50 % by using the non-Newtonian models, but its metrics based on time and surface averaged values are less affected — the maximum relative difference among the cases is 7 % for the Casson model. On the other hand, the surface-averaged OSI is underestimated by more than 30 % by the non-Newtonian models. These results suggest that it is recommended to investigate different blood rheology models in IAs simulations when specific parameters to characterize the flow are needed, such as peak-systole WSS and OSI.
Keywords: Intracranial aneurysms; Hemodynamic variables; Numerical simulations; Blood Rheology